Prevalence and characteristics of Staphylococcus aureus and methicillin‐resistant Staphylococcus aureus nasal colonization among a community‐based diabetes population in Foshan, China. Issue 3 (15th December 2016) - Lin, Jialing; Xu, Ping; Peng, Yang; Lin, Dongxin; Ou, Qianting; Zhang, Ting; Bai, Chan; Ye, Xiaohua; Zhou, Junli; Yao, Zhenjiang
Abstract: Aims/Introduction: Evidence suggests that diabetes might cause an increase in colonization of Staphylococcus aureus ( S. aureus ) and methicillin‐resistant S. aureus (MRSA) in community settings. We carried out a cross‐sectional study to determine the prevalence and influencing factors of S. aureus and MRSA nasal colonization among a community‐based diabetes population, and to identify the characteristics of the isolated strains. Materials and Methods: A total of 956 participants from 11 community settings were included in the study. Results: Of the 529 diabetes participants, 46 were colonized with S. aureus and 22 were colonized with MRSA. Of the 427 non‐diabetes participants, 25 were colonized with S. aureus and 12 were colonized with MRSA. Men (odds ratio 0.45, 95% confidence interval 0.20–0.99, P = 0.047) were less likely to have S. aureus nasal colonization, and those with well‐controlled blood glucose (odds ratio 2.04, 95% confidence interval 1.01–4.13, P = 0.047) among the diabetes population were more likely to have S. aureus nasal colonization. The proportion of multidrug‐resistant S. aureus strains in the diabetes population (52.17%) was higher than that in the non‐diabetes population (28.00%; χ 2 = 3.848, P = 0.050). The most common clonal complex type and Staphylococcal chromosome cassette mec type of MRSA in diabetes population was clonal complex 5 (40.91%) and type IV (27.27%), respectively. The proportion of Panton–Valentine leukocidin gene in MRSA strains was 17.65%. There was great sequence type diversity in MRSA strains. Conclusions: The prevalence of MRSA in the community‐based diabetes population was moderate, and the high proportions of multidrug‐resistant S. aureus strains and diverse molecular characteristics in the diabetes population should be noticed.